1983
DOI: 10.1246/cl.1983.1097
|View full text |Cite
|
Sign up to set email alerts
|

A FACILE OXIDATIVE LACTONIZATION OF 1,ω-Diols WITH SODIUM BROMITE

Abstract: A practically useful method for the oxidation of 1,ω-diols to lactones is described. The scope and limitations are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To date, various reaction systems have been developed, which include stoichiometric oxidation using Na 2 Cr 2 O 7 , 3 Br 2 -HMPT, 4 Ca(OCl) 2 , 5 NaOCl, 5 NaBrO 2 , 6 NaBrO 3 -NaHSO 3 , 7 PCC-Al 2 O 3 , 8 and so on. Recently, Bobbitt et al reported oxidative dimerization of polyfunctional primary alcohols using oxoammonium salts.…”
Section: Methodsmentioning
confidence: 99%
“…To date, various reaction systems have been developed, which include stoichiometric oxidation using Na 2 Cr 2 O 7 , 3 Br 2 -HMPT, 4 Ca(OCl) 2 , 5 NaOCl, 5 NaBrO 2 , 6 NaBrO 3 -NaHSO 3 , 7 PCC-Al 2 O 3 , 8 and so on. Recently, Bobbitt et al reported oxidative dimerization of polyfunctional primary alcohols using oxoammonium salts.…”
Section: Methodsmentioning
confidence: 99%
“…To retard the undesired reaction, the reaction of compound 11 was conducted with dihydropyran (DHP) to give a tetrahydropyran-2-yl ether 13, which was readily dehydroiodated with DBU to furnish olefin 14. Furthermore, deprotection of ether 14 with p-TsOH in CH,C12-MeOH gave in 78% overall yield (from iodo lactone 11) 6-lactone alcohol 15, Jones oxidation of which in acetone afforded 6-lactonic acid 16 in 63% yield. ?…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this assumption, conversion of lactone 16 into a known y-lactam 19 was performed. Thus, compound 16 was transformed into an azide in the usual manner (ClCO,Et, Et,N; NaN,, water) followed by Curtius rearrangement with benzyl alcohol in boiling toluene to give the benzyl carbamate 17 in 72% yield. Reductive debenzylation of carbamate 17 and successive acid treatment afforded amino ester 18, which was heated in EtOH for 10 h to furnish lactam 19 in 86% yield (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods for the dimeric esterification of primary alcohols, such as benzyltrimethylammonium tribromide in carbon tetrachloride, bromine-potassium bromate in water, sodium hypochlorite in acetic acid, sodium dichromate-sulfuric acid, calcium hypochlorite in acetonitrile-acetic acid, and sodium bromite in acetic acid have been employed for this propose [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%